Analisis Pelanggaran Maksim Sopan Santun dan Tindak Tutur Direktif dalam Anime Himouto Umaru Chan - Diah Soelistyowati; Ninik Elika (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2021)
The topic of this research is about directive speech act and the violations of politeness maxim in one of the famous anime. The speech act in this anime shows us about daily life activity. Both speakers and hearers can break people’s politeness in communication and make someone’s to do something. The aim of this research is to describes directive speech act and the violations of politeness maxim in anime entitled Himouto Umaru Chan. This research used descriptive qualitative method. For the speech act theory, the researcher used the theory proposed by Searle and Namatame and also politeness principal theory proposed by Geoffrey Leech. The data were taken from the speaker named Himouto Umaru Chan that used directive speech act and also shows the violations of politeness maxim in her speech. In collecting the data, the researcher employ listening and note-taking technique. It can be concluded that the most occurance data of directive speech act is meirei and the violations of tact maxim is when Umaru chan make some orders to her brother for her personal needs.